Effect of Cadmium on Cellular Ultrastructure in Mouse Ovary. (3rd September 2015) - Wang, Ying; Wang, Xuejuan; Wang, Yanwu; Fan, Rong; Qiu, Chao; Zhong, Shan; Wei, Lei; Luo, Daji
Abstract: This study aimed at analyzing the cytotoxicity and pathological effects of cadmium on the ovary. Our studies revealed that cadmium was deposited in the mouse ovary after 8 d cadmium injection in vivo. Also, the increase in the rate of body weight was slowed, while the gonadosomatic index was reduced in the CdCl2 group, compared with the control group. Meanwhile, cadmium affected the maturation of follicles, the degradation of corpus luteum, the arrangement of follicles and corpus luteum, and increased the number of atresia follicles. Besides, under the electron microscope, chromatin margination, karopyknosis, swelling of mature cisternae of Golgi apparatus, mitochondrial cristae disappearance, and swelling of the rough endoplasmic reticulum can be observed in the CdCl2 group mice. Collectively, our findings elucidated the morphological mechanism that the exposure of cadmium changed the ultrastructure of cells in ovary tissues.